EFFECT OF BARLEY PROLAMIN HYDROLYSATE TO INHIBIT ACE I CAPACITY - Abadi, Firas; Naser, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The aim of this work was to evaluate the potential of local barley (class Ibaa 99), an underutilized plant, as a potential functional ingredient in blood pressure (BP) treatment and health promotion. For this purpose, the ability barley prolamin isolates hydrolysate (BPIH) to inhibit Angiotensin-converting enzyme I (ACE I) was studied. Prolamin was extracted from barley, then digestion by pepsin and the effect of successive purifications using gel filtration sephadex [GF-(G25)] technology on the efficiency of ACE I inhibition capacity was studied. The results showed the efficiency of the pepsin in hydrolyzing barley prolamins, and the percentage of degree hydrolyses (DH %) increased with time. The ACE I inhibition value increased in parallel with the increase in DH %, reaching the highest value (81.44%) after 8 hours. In addition, inhibition capacity value increased after purification of BPIH using GF-(G25) to reach 88.74% in the first purification then 92.36% after the second 1. Increase inhibition was proportional to rise concentration of low M.Wt peptides of the BPIH, as the M.Wt of the peptides was less than 3.484 kDa in the first step of GF-(G25) and less than 1.470 kDa in the second step of GF-(G25),  with an increase in concentration the hydrophobic amino acids (A.As) in these peptides (33 , 52.4%), respectively.